Filter Matching for Digital Data Transmission - Liepkalns, D.; Hermanis, E. (Elektronika ir Elektrotechnika, 1999)
To minimise frequency band used for data transmission filters with impulse response close to sinc-function are widely used. Therefore, in transmitters and receivers the Root Raised Cosine filters are used. Serial combination two such filters are not sufficient for such data link. In this paper filters similar to sinc filters are proposed, which are based on Bessel function ratio to time. These filters allow for more efficient transmitter frequency range restriction and matching several serially interconnected filters. Besides that they are more convenient for implementation. Jointly with the respective transversal filter they provide for the required transient dynamics in the low frequency part of the receiver.